IMPROVING STUDENTS’ READING COMPREHENSION THROUGH KNOW, WANT TO KNOW, LEARNED AND HOW STRATEGY - Abd. Rifai (Jurnal Ilmiah Kesmas -IJ, 2024)
The result of preliminary study done by the researcher at STIKIJ Palu revealed that in most of the classroom activities, the teacher focused on testing the students‟ comprehension rather than in teaching the effective strategies of understanding an English text.Reading comprehension lessons had commonly centered on reading a passage of text followed by questions which was only intended to find out whether the students can answer or not, rather than to produce reading skill. The objective of this research is to improve the students‟ reading comprehension ability through the Know,Want to Know, Learned and How(KWLH) strategy. The design of this research is collaborative classroom action research which is carried out in two cycles.The subjects of the study are 42seventh semester students of Public Health study program at STIKIJ Palugathered by using observation sheets, field notes, reading test and questionnaires. The strategy was considered successfulif 100% of the students achieved the scores equal to or more than 70 in the range 1-100 in their reading comprehension. Also, 100% of the students actively involved in the teaching and learning process.After conducting the implementation of KWLH strategyit can be concluded that this strategy has improved the reading comprehension ability of seventh semester students of Public Health study program at STIKIJ Palu